Phrynobatrachus pintoi Hillers, Zimkus & Rödel, 2008 (Amphibia: Anura: Phrynobatrachidae): additional morphological and distribution data - Rödel, Mark-Oliver; Doumbia, Joseph; Kouamé, N’goran Germain; Sandberger, Laura (Zootaxa, 2011)
Currently 14 Phrynobatrachus species are known to occur in Guinea (Frétey 2008; Frost 2011). The recently discovered species, Phrynobatrachus pintoi Hillers, Zimkus and Rödel, 2008, was described from the Boké region, north-western Guinea (Hillers et al. 2008). Although this description comprised distinct morphological and genetic characters, it was only based on one, subadult specimen. Further data on the species morphological variability, its biology and distribution, are thus needed. During a survey from 28 September to 20 October 2010 in the Télimélé region, north-western Guinea, we recorded this species at three additional localities. The respective data are presented herein.